(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
The actinopterygians Allolepidotus bellottii (Rüppell), Furo trottii (Balsamo Crivelli, 1839) and Perleidus altolepis (Deecke, 1889), so far known from the Perledo Member (upper member of the Perledo-Varenna Formation), are here redescribed on the basis of well-preserved material coming from the late Ladinian Kalkschieferzone of Ca’ del Frate (Viggiù, Varese) and Meride (Canton Ticino, Switzerland). These new finds in the Kalkschieferzone are particularly important because they allow the first detailed anatomical description of Allolepidotus bellottii and the complete anatomical restoration of Perleidus altolepis; the presence of the caturid Furo in the Middle Triassic, which has previously been questioned, is confirmed. Besides the anatomical descriptions, the complicated and problematical nomenclature adopted by previous authors for the species of the Perledo Member is discussed. The stratigraphical distribution of the genus Perleidus is questioned, as the Triassic species previously ascribed to this genus are here considered as not related to it. Finally, a new genus of Perleidiformes is erected.